Networks for technology transfer: linking HEIs and SMFs. (4th August 2014) - Jones, Oswald; Tang, Nelson
It is increasingly recognised that networks are central to the effective transfer of technology. This paper examines the way in which such networks are established by HEIs (Higher Education Institutes). Equally significant is the acceptance that Small– and Medium–Sized Firms (SMFs) make valuable economic and social contributions through their distinctive capabilities for innovation. However, SMFs rarely possess adequate R&D assets and generally need to acquire new technologies from external sources. It is suggested that collaboration between HEIs and SMFs has considerable potential for strengthening innovatory activity in the UK. However, there is very little detailed information on the way in which networks are established and maintained by HEIs. Questionnaire data on the extent and importance of links with SMFs were obtained from 37 HEIs. In addition, interviews were carried out with the individuals responsible for marketing science and technology in five HEIs. Every HEI in the sample had established contacts with SMFs and almost 70% claimed that such alliances had made at least a 'moderate' impact on technology transfer. Furthermore, this figure increased to 95% when respondents were asked the likely impact on HEIs in the next five years. The interviews provided detailed information on the processes by which HEIs create transfer technology network links with SMFs.